Entrepreneurship : FNF Hash Services / Fazarudin A.Wahab, Nordin Ahmad Khalid and Mohd. Fadly Shah Chik - A.Wahab, Fazarudin; Khalid, Nordin Ahmad; Chik, Mohd. Fadly Shah (2008)
The business plan is the document that will guide of making business project. In this executive summary it contained the summary for the business plan that we prepared. Our business is specialized on services. The service that we plan for business is hair cut service that is name FNF Hair Service.